PENGARUH PANDEMI COVID-19 TERHADAP KEBIJAKAN MANAJEMEN KEUANGAN DAN NILAI PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Burhanudin Burhanudin; Sri Darwini; Laila Wardani (Master of Management, Mataram University, 2022)
The impact of the Covid-19 pandemic was not only felt in the field of health, but also had an impact on the economy. This research aims to find out the difference between Funding Policy (DAR), Investment Policy (FAR), Dividend Policy (DPR) and company value (Tobin's Q) before and during the Covid-19 pandemic in LQ 45 Companies listed on IDX. The results showed that there was no significant difference in DAR, FAR, DPR and Tobin's Q before and during the Covid-19 pandemic in the LQ 45 Company listed on the IDX. Before covid 19 DAR and DPR had a positive and significant effect on Tobin's Q. While during covod 19 only dpr had a positive and significant effect on Tobin's Q LQ 45 company registered with idx. Keywords: Covid-19 Pandemi, Financing Policy, Investment Policy, Dividend Policy and Corporate Value